Towards the revision of EC8: Proposal for an alternative site classification scheme and associated intensity dependent spectral amplification factors. Issue 126 (November 2019) - Pitilakis, Kyriazis; Riga, Evi; Anastasiadis, Anastasios; Fotopoulou, Stavroula; Karafagka, Stella
Abstract: The paper presents an alternative site classification scheme and associated intensity dependent spectral amplification factors, aiming to contribute to the ongoing revision of Eurocode 8. The new classification scheme, introducing among the main classification parameters the fundamental period T0 of the site, is an evolution of the recent work by Pitilakis et al. (2013) [1], while the main features of the amplification factors and the new seismic design actions are summarized in the use of two anchoring spectral values, for short (0.2–0.3 s) and intermediate (1.0 s) periods, instead of only one of the present version of Eurocode 8 (i.e. effective ground acceleration), and the scalar intensity variation of site amplification factors to account for soil nonlinearity. The work is based on a comprehensive analysis of a worldwide database of strong ground motion records from sites which dispose a very well-documented soil profile down to the seismic bedrock (Vs>800 m/s). Highlights: New site classification scheme, elastic spectra and amplification factors for EC8. Main classification parameter is the fundamental period of the site. Use of two anchoring spectral values for short and intermediate periods. Scalar intensity variation of site amplification factors for each soil class.